Making digital transformation work for all in Chile - Garda, Paula (OECD Economics Department Working Papers, 2021)
The sanitary crisis, created by the outbreak COVID-19, is accelerating Chile's digital transformation, which has seen a surge in e-learning, streaming, online shopping and marketing and teleworking. The digital transformation has the potential to revamp productivity and inclusiveness, although it comes with adoption barriers and transition costs. Connectivity has increased substantially in the last decades, and the country is ahead of the region. However, fixed high-speed broadband adoption, essential for the digital transformation, lags behind. Firms have started to adopt digital technologies but micro firms and SMEs are well behind. Rural areas have lower connectivity and many workers lack the skills to thrive in the digital world. Lowering the entry barriers in the communication sector and making regulations simpler and clearer would ease infrastructure deployment. Targeted policies for SMEs, such as development of sources of financing or specific programmes for adopting digital tools, would help them access and use digital tools, increasing productivity. Reforms to the innovation ecosystem, competition and the regulatory framework are also needed. To reap the benefits of digitalisation for all, it is necessary to continue investing in quality foundational skills, adult and lifelong learning and in high-skilled ICT specialists. Labour market policies need to be adapted to face the challenges and exploit the benefits posed by the digital transformation. An effective safety net would address possible labour market disruptions